Factors determining the amount of working capital requirements for business sustainability at UD SAS in Oebufu District Kupang City-NTT - Adrianus Aluman (Jurnal Mantik, 2023)
Working capital is crucial in opening or developing a business. Working capital can be seen from its quantity, quality and function. In this study we will use the functional concept. Many factors influence the amount of working capital needed. including: Nature or type of company, time required to produce goods, purchase or sales conditions, inventory turnover time, receivables turnover rate, sales volume, seasonal and cyclical factors. However, the factors that determine the size of working capital requirements related to company operations have not been seen as variables that are very important in maintaining the continuity of company activities. The research took the form of a case study conducted at CV SAS, by collecting documents in the form of financial reports, interviews with company leaders and owners. The data is analyzed using comparative techniques, including determining the company's operational needs, cash turnover time, accounts receivable turnover time, inventory turnover time, and determining the amount of working capital requirements. The research results show that the main determining factor is the length of capital turnover time through the purchasing process, waiting time (purchase, storage and sales) while the capital required each period is IDR 64,000,000.